ANTI-INFLAMMATORY ACTIVITY OF AQUEOUS BARK EXTRACT OF THESPESIA POPULNEA IN RATS - U.D.S. Sewwandi; E.R.H.S.S.Ediriweera; W.D.Ratnasooriya (International Journal of Ayurveda and Pharma Research, 2020)
This study examined the oral anti-inflammatory potential of aqueous extract of Thespesia populnea Linn bark. Soland. Ex. Corr. (Family: Malvaceae) which is used by Sri Lankan native practitioners to treat skin ailments and arthritis. This was tested in conscious male Wistar rats using carrageenan induced paw edema model and three oral doses; 1250, 2500 and 5000mg/kg. Indomethacin was used as the reference drug. The result showed that the aqueous extract of bark significantly P<0.05 and dose dependently inhibited both early (1-2 h) and late phase (4-5 h) of inflammation in the carrageenan model. In addition, it inhibited the intermediated phase (3 h). The anti-inflammatory activity of the highest doses of extract was comparable to that of indomethacin. The extract did not display overt signs of toxicity and was neither hepatotoxic, renotoxic nor hematotoxic even with chronic administration. It is concluded that aqueous bark extract of Thespesia populnea can function as an orally active, safe and potent anti-inflammatory agent.